Leptomeningeal metastases of esophagogastric junction adenocarcinoma – case report and treatment review - Olesiński, Tomasz; Jeziorski, Krzysztof; Szawłowski, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2007)
Oesophagogastric junction adenocarcinoma usually disseminates to the abdominal lymph nodes, peritoneum (peritoneal carcinomatosis) or with blood to the distant organs (such as liver, lung, bones or central nervous system); leptomeningeal metastases are rare. A case report of a 49-year-old male with disseminated oesophagogastric junction adenocarcinoma (with liver, abdominal lymph nodes and leptomeningeal metastases) is presented. As a clinical representation progressive dysfunction of the central and peripheral nervous system has been observed. Patterns of failure of gastric adenocarcinoma treatment and clinical value of prognostic factors are evaluated. Oesophagogastric junction adenocarcinoma dissemination and leptomeningeal metastases diagnostic and treatment capabilities are discussed. Conclusions: Leptomeningeal metastases of oesophagogastric junction adenocarcinoma are rare and available treatment (radiotherapy, chemotherapy – systemic or local) is inefficient.